1997
DOI: 10.1002/(sici)1097-4601(1997)29:5<349::aid-kin5>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of Cl-atom reactions with selected aromatic compounds using the photochemical reactor-FTIR spectroscopy technique

Abstract: Relative rate constant measurements have been carried out on the Cl-atom reactions with benzene, chlorobenzene, toluene, xylene, and styrene in 740 torr of air at room temperature (295 K), using the photochemical reactor-FTIR spectroscopy technique. The Cl atoms were generated by the UV photolysis of Cl 2 , and the reference compounds were CHF 2 Cl for benzene and chlorobenzene and isobutane for toluene, xylene, and styrene. Using the absolute rate constants for these two reference compounds reported in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 31 publications
6
47
0
Order By: Relevance
“…Sokolov et al determined an upper limit of 2.5 x 10 -16 cm 3 molecule -1 s -1 for HCl formation at room temperature [8]. This is below a prior measured total rate constant of 9.8 x 10 -16 cm 3 molecule -1 s -1 by Shi and Bernhard [9]. A potential reaction path under these conditions is formation of dichlorocyclohexadienyl radicals by addition.…”
Section: Introductionmentioning
confidence: 86%
“…Sokolov et al determined an upper limit of 2.5 x 10 -16 cm 3 molecule -1 s -1 for HCl formation at room temperature [8]. This is below a prior measured total rate constant of 9.8 x 10 -16 cm 3 molecule -1 s -1 by Shi and Bernhard [9]. A potential reaction path under these conditions is formation of dichlorocyclohexadienyl radicals by addition.…”
Section: Introductionmentioning
confidence: 86%
“…For light alkenes, there may be an additional impact on δ 13 C due to reaction with ozone (Iannone et al, 2003) (Shi and Bernhard, 1997), the KIE measurement method used in this work is not suitable for this reaction.…”
Section: Atmospheric Relevancementioning
confidence: 99%
“…b Experimental rate constant calculated using literature rate constants and uncertainties for the reference compound (Atkinson and Aschmann, 1985;Coquet and Ariya, 2000;Ezell et al, 2002;Fantechi et al, 1998;Shi and Bernhard, 1997;Smith et al, 2002;Stutz et al, 1998;Wallington et al, 1989) Uncertainty shown is the error of the mean KIE value for compounds with two KIE measurements, and the uncertainty from the standard error of the plot of Equation (1) for compounds with only one KIE measurement. b Iannone et al, (2003) c Mean Cl k value with 1σ standard error of the k values determined using relative rate analysis for compounds measured more than once.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the late stage of irradiation, radical reactions play very important role for chlorinated aromatic hydrocarbon decomposition. Because rate constants of Cl radicals with chlorinated aromatic hydrocarbons (usually 1.0 × 10 -15 ~ 1.0 × 10 -16 ) (Shi & Bernhard, 1997) are much smaller than those of OH radicals ( 1.0 × 10 -12 ~1.0 × 10 -13 ), Cl radical addition reaction followed by peroxyl radical reaction pathway is not so important for chlorinated aromatic hydrocarbon decomposition in air mixture; on the contrary, OH radical reaction pathway is more important for chlorinated aromatic hydrocarbon decomposition in low or high humidity air mixture (Sun et al, 2007c …”
Section: General Mechanism Of Chlorinated Aromatic Hydrocarbons (Cl-amentioning
confidence: 99%